Photoaffinity Labeling and Quantitative Chemical Proteomics Identify LXRβ as the Functional Target of Enhancers of Astrocytic apoE - Seneviratne, Uthpala; Huang, Zhen; am Ende, Christopher W.; Butler, Todd W.; Cleary, Leah; Dresselhaus, Erica; Evrard, Edelweiss; Fisher, Ethan L.; Green, Michael E.; Helal, Christopher J.; Humphrey, John M.; Lanyon, Lorraine F.; et al. (Cell chemical biology, 2021)
Utilizing a phenotypic screen, we identified chemical matter that increased astrocytic apoE secretion in vitro. We designed a clickable photoaffinity probe based on a pyrrolidine lead compound and carried out probe-based quantitative chemical proteomics in human astrocytoma CCF-STTG1 cells to identify liver x receptor β (LXRβ) as the target. Binding of the small molecule ligand stabilized LXRβ, as shown by cellular thermal shift assay (CETSA). In addition, we identified a probe-modified peptide by mass spectrometry and proposed a model where the photoaffinity probe is bound in the ligand-binding pocket of LXRβ. Taken together, our findings demonstrated that the lead chemical matter bound directly to LXRβ, and our results highlight the power of chemical proteomic approaches to identify the target of a phenotypic screening hit. Additionally, the LXR photoaffinity probe and lead compound described herein may serve as valuable tools to further evaluate the LXR pathway. [Display omitted] •A phenotypic screen identifies novel chemical matter regulating apoE secretion in vitro•Chemical biology strategy identifies LXRβ as the functional target of phenotypic hit•Study highlight the critical nature of counter-screening strategy as part of hit triage•Photoaffinity probe and potent lead may serve as valuable tools to probe LXR biology Phenotypic screens can potentially deliver first-in-class drugs. Seneviratne et al. describe a screen and hit triage strategy to identify small molecule activators of apoE secretion in human astrocytes. The team applied comprehensive chemical biology tactics for target deconvolution to identify LXRβ as the target of the lead chemical matter disclosed.